Pemberdayaan Santri melalui kreasi Batik Nusantara Sundra Jagat Pondok Pesantren Sunan Drajat Lamongan - Muhammad Haris; Abdul Khamid; Afif Fudin; Abul A’la Al Ma’adudi; Moh. Mu’amarul Ma’aruf; Moh. Lutfi Izaki; Mohammad Lucky P (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
This assistance is intended to develop the assets of the al maliki boarding school, Sunan Drajat Islamic Boarding Schol, Lamongan, to become a pilot dormitory in the field of developing the potential for making Indonesian batik using the Training of Trainer or TOT method by providing understanding materials, then followed by direct practice by students of Al Maliki Dormitory. Based on the results of the assistence of the Training of Trainer or TOT method, it can be concluded that assistance in empowering students through the creation of Nusantara batik santri Al Maliki in training to make a superior product for students in the Al Maliki dormitory will not succeed if there is no cooperation and active participation from the mentoring subject, dormitories, foundations, especially institutions. in this era of reform and the spirit of decentralization, Islamic boarding schools need to be managed more proactively for the future of santri as quality human resources and habe good morals. to achieve this goal, competencies are needed as profesional human resu.